Global Growth Processes: Technology Diffusion, Catching-up and Effective Demand - Michael Landesmann; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2004)
This paper analyses two issues that were characteristic of the global growth processes of the 1980s and 1990s (i) an important diffusion process of a new general purpose technology (GPT) and (ii) a speed-up of catching-up of a sub-group of developing economies (South East Asia, later China and India) in an era of increasing globalization. Both these factors should in principle have given a boost to global economic growth; however, for quite some time, actual growth has been perceived as being in a more precarious state in advanced economies than in the earlier post-war period. The paper develops a dynamic model of integrated economies (through trade and FDI) which attempts to address the above developments. The model has Schumpeterian and Keynesian features in that it depicts the income distributional shifts which might accompany the diffusion processes of new technologies (Schumpeterian innovational rents) and discusses effective demand problems which can arise both as a result of income distributional changes on the one hand and catching-up processes on the other. We start with a stylized description of a competitive situation between two sets of advanced economies (say, the US and the EU) which are characterized by different behavioural responses in labour and product markets and where one region (the US) experiences the diffusion process of the new GPT earlier than the other region (the EU). The introduction of a new technology shifts the macro-distribution of income towards profits and the reliance of the growth process towards the investment (rather than consumption) component of effective demand. Differences in the workings of the labour and product markets affect the extent of these macro-distributional shifts. In addition the model is one in which the two sets of economies are integrated through trade and foreign direct investment flows. Transitory paths describe the impact of changing cost competitiveness and profitability positions upon net trade balances and net foreign direct investment flows. This amounts to leakages and injections in the two sets on economies which we track in terms of evaluating differences between 'potential' and 'actual' growth paths. The second issue we try to analyse with the model is the impact of catching-up processes of a significant group of developing economies. Successful catching-up processes are characterized by fast productivity growth, by even stronger transitory wage-productivity growth gaps and hence macro-distributional shifts. This has implications for international direct investment flows and for global effective demand structures with the added dimension that the weight of the group of catching-up economies in the global economy is growing rapidly, which in turn affects the response mechanisms in the advanced economies. The focus remains on the exploration of the impact that different behavioural characteristics of labour and product markets have on the growth paths of the two sets of economies. The model allows for endogenous exchange rate dynamics, some endogeneity of productivity growth and changing international 'sourcing' patterns of intermediate inputs.
Keywords: E1; E12; E22; E25; F43; O11; O19; O41; 330; international competition; catching-up; technology diffusion; Schumpeterian and Keynesian dynamics; dynamic modelling